Dependence of Uniaxial Compressive Strength of Sanjome Andesite on Loading Rate and Water Saturation - Minami KATAOKA; Kimihiro HASHIBA; Katsunori FUKUI (Journal of MMIJ, 2018)
It is known that the rock strength increases with an increase in loading rate. Many studies on the loadingrate dependence of rock strength have been performed under two environments, namely water-saturated and airdried conditions, and the loading-rate dependence has not been investigated well under the conditions of various water saturations observed in situ rock masses. In addition, the quantitative relation between the loading-rate dependence and water saturation has not been examined. In this study, the uniaxial compression test of Sanjome andesite under various water saturations was carried out and the dependence of the strength on the loading rate and water saturation was investigated. The test was performed with alternating two loading rates and the strength corresponding to each loading rate was determined from a single specimen. The test results show that the strength increase with a ten-fold increase in loading rate is almost the same under various water saturations and that the strength increases with a decrease in water saturation. Based on the test results, the theory to explain the dependence of the strength on the loading rate and water saturation was suggested. The variation in the strength was discussed to validate the theory.